2022
DOI: 10.3390/ijms231911090
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid Micellization and Adsorption Properties

Abstract: Biosurfactants are naturally occurring amphiphiles that are being actively pursued as alternatives to synthetic surfactants in cleaning, personal care, and cosmetic products. On the basis of their ability to mobilize and disperse hydrocarbons, biosurfactants are also involved in the bioremediation of oil spills. Rhamnolipids are low molecular weight glycolipid biosurfactants that consist of a mono- or di-rhamnose head group and a hydrocarbon fatty acid chain. We examine here the micellization of purified mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
(134 reference statements)
1
5
0
Order By: Relevance
“…Surfactants with low CMC are generally considered effective as less amounts would be required to form micelles and subsequently perform surface activities, such as foaming and emulsification, in skincare formulations [149][150][151]. The significant difference in CMC between glycolipids and synthetic surfactants has been reported in several studies, where the authors indicated that the CMC of sophorolipid and rhamnolipid congeners were at least tenfold lower than the CMC of the synthetic surfactants utilised in the same study; this demonstrates a potential preferential use of these glycolipids over synthetic surfactants in skincare applications as less amounts would be required to achieve the needed surface activity [19,[152][153][154]. However, it should be acknowledged that glycolipids are readily biodegradable and can lose some activity with time depending on the concentration at which they are prepared, batch storage conditions, and variation in-house extraction/purification methods [155].…”
Section: Limited In Vitro Studies On Potential Benefits Of Glycolipid...supporting
confidence: 53%
“…Surfactants with low CMC are generally considered effective as less amounts would be required to form micelles and subsequently perform surface activities, such as foaming and emulsification, in skincare formulations [149][150][151]. The significant difference in CMC between glycolipids and synthetic surfactants has been reported in several studies, where the authors indicated that the CMC of sophorolipid and rhamnolipid congeners were at least tenfold lower than the CMC of the synthetic surfactants utilised in the same study; this demonstrates a potential preferential use of these glycolipids over synthetic surfactants in skincare applications as less amounts would be required to achieve the needed surface activity [19,[152][153][154]. However, it should be acknowledged that glycolipids are readily biodegradable and can lose some activity with time depending on the concentration at which they are prepared, batch storage conditions, and variation in-house extraction/purification methods [155].…”
Section: Limited In Vitro Studies On Potential Benefits Of Glycolipid...supporting
confidence: 53%
“…The aggregation behavior of R1 and R2 has also been rationalized in some cases through the calculation of the critical packing parameter ( cpp ) [ 193 , 194 ], but very different values are reported in different papers, with cpp values ranging from 0.24 [ 172 ] to 1 [ 144 ] for R1 and from 0.27 [ 172 ] to 0.73 [ 179 ] for R2.…”
Section: Aggregation Behaviormentioning
confidence: 99%
“…In most cases, the carboxyl group of the distal β-hydroxy fatty acid chain remains free; few congeners, however, have this group esterified with a short alkyl group [ 55 ]. The high structural diversity of different rhamnolipid molecules, resulting in a large pool of rhamnolipid homologs that approaches 60 structures, arises from the numerous combinations of the number of rhamnose moieties and the nature of the aliphatic chains, which may be saturated, monosaturated, or polyunsaturated and branched, with chain length varying from C 8 to C 16 [ 55 , 144 ]. As an example, Table 1 presents the rhamnolipid congeners produced by Pseudomonas aeruginosa grown using two different carbon sources: glycerol and soy [ 145 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, rhamnolipid is a mixture of up to 26 different compounds [ 21 ]. Therefore one can find differ opinions on its adsorption and aggregation activity in the literature [ 22 , 23 ]. It should be noted that most of the available papers deal with mono-rhamnolipid.…”
Section: Introductionmentioning
confidence: 99%